A study to assess the effect of nutritional supplementation on the hemoglobin level and the associated signs and symptoms of the students identified with anaemia in selected colleges of SNDT Womens’ University Mumbai - Padma Satishrao Mugal (Emerging Trends in Personalized Medicines, 2024)
The purpose of this study was to assess the effects of nutritional supplements on haemoglobin levels and related symptoms among students at SNDT Women's University in Mumbai who had been diagnosed with anaemia in a few particular institutions. Non-occurrence A sample of thirty anaemic students was selected via easy sampling. With a one-group pre-test-post-test methodology, the study used a descriptive evaluative design. Data collecting instruments included measurement devices, opinion questionnaires, inventory checklists, and observation checklists. To assess the reliability of the observation checklist, inter-rater reliability tests were performed. The design's viability and practicality were confirmed by a preliminary analysis carried out before the main investigation. Nutritional supplements were given to several groups for either 15 or 30 days during the course of a month-long data collection session. After 15 and 30 days of supplementation, the results showed a considerable increase in haemoglobin levels. Following supplementation, related anaemia symptoms and indicators decreased. The majority of students reported few side effects from the supplementation and did well to tolerate it. Before taking supplements, individuals' iron consumption was found to be unsatisfactory based on an analysis of their food intake. The majority of students expressed enthusiasm in spreading the intervention to others and had favourable thoughts regarding the taste and efficacy of the supplementation. The study's findings showed that iron-rich dietary supplements can help college students with anaemia symptoms by raising haemoglobin levels and reducing iron deficiency. Though some were worried about possible adverse effects on the gastrointestinal system, the supplements proved to be well-tolerated and even helped to improve bowel habits. The potential for improving the health condition of anaemic students through this intervention underscores the significance of addressing nutritional deficits in this population.
Keywords: Anemia; Nutritional Supplementation; SNDT Women's University; college students; hemoglobin